Perbandingan Kalkulasi Gizi Makro Anak Sakit Berdasarkan Recommended Dietary Allowance dan Angka Kecukupan Gizi di RSUP Sanglah Denpasar: Comparison of Macronutrients Calculation in Sick Children According to Recommended Dietary Allowance and Angka Kecukupan Gizi in Sanglah General Hospital, Denpasar - I Made Samitha Wijaya; I Gusti Lanang Sidiartha; I Gusti Ayu Putu Eka Pratiwi; Ida Ayu Surya Agustini (Amerta Nutrition, 2023)
Background: Optimal nutrition care in hospitalized children is essential to improve the prognosis of diseases. One strategy is the implementation of Pediatric Nutrition care (PNC) in all hospitalized children. Objectives: to compare the macronutrient calculation in PNC with Angka Kecukupan Gizi (AKG). Methods: A cross-sectional study was conducted in hospitalized children aged six months to 18 at the Pediatric Ward Sanglah General Hospital, Denpasar, Bali, from January to December 2020. Macronutrient calculation in PNC using Recommended Daily Allowance (RDA) was compared with AKG in all subjects during hospitalization. The difference was analyzed using a paired-t test with significance if p-value < 0.05. Results: A total of 97 subjects were included, 52 male (53.6%) and 45 female (46.4%). Most of the subjects were aged above five years old (58.8%), well nourished (49.5%), had acute diseases (60.8%), and length of stay of fewer than seven days (66%). The mean calculation of carbohydrates, lipids, and protein according to RDA and AKG were 162.3 g vs. 250 g (p<0.001), 56.2 g vs. 65.9 g (p<0.001), and 60.9 g vs. 40 g (p<0.001), respectively. Conclusions: Protein calculation using RDA is significantly higher, conversely to carbohydrate and lipids is lower. Sick children commonly need more protein against their diseases, so using RDA to calculate the macronutrient requirement is recommended.